2018
DOI: 10.1016/j.mce.2018.02.005
|View full text |Cite
|
Sign up to set email alerts
|

Pyk2 deficiency potentiates osteoblast differentiation and mineralizing activity in response to estrogen or raloxifene

Abstract: Bone remodeling is controlled by the actions of bone-degrading osteoclasts and bone-forming osteoblasts (OBs). Aging and loss of estrogen after menopause affects bone mass and quality. Estrogen therapy, including selective estrogen receptor modulators (SERMs), can prevent bone loss and increase bone mineral density in post-menopausal women. Although investigations of the effects of estrogen on osteoclast activity are well advanced, the mechanism of action of estrogen on OBs is still unclear. The proline-rich t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 84 publications
0
8
0
Order By: Relevance
“…Adherent-BMCs were cultured for 10 days in α-MEM supplemented with 10% FBS and 1% penicillin/streptomycin in the presence of 50 μM ascorbic acid and 10 mM β-glycerol phosphate, as previously described (Posritong et al, 2018). Cells were fixed with 3.7% paraformaldehyde in PBS for 1 hour, rinsed twice with distilled water, and stained for 10 min with 40 mM Alizarin Red S (pH 4.2) at room temperature under shaking.…”
Section: Osteoblast Mineralization Assaymentioning
confidence: 99%
“…Adherent-BMCs were cultured for 10 days in α-MEM supplemented with 10% FBS and 1% penicillin/streptomycin in the presence of 50 μM ascorbic acid and 10 mM β-glycerol phosphate, as previously described (Posritong et al, 2018). Cells were fixed with 3.7% paraformaldehyde in PBS for 1 hour, rinsed twice with distilled water, and stained for 10 min with 40 mM Alizarin Red S (pH 4.2) at room temperature under shaking.…”
Section: Osteoblast Mineralization Assaymentioning
confidence: 99%
“…In eosinophils, Pyk2 is not required for integrin-mediated adhesion, but is essential for β2 integrin-mediated spreading and migration [ 28 ]. Pyk2 is involved in normal bone remodeling [ 29 , 30 , 31 ]. Pyk2 −/− mice exhibit increased bone mass due to increased bone formation, resulted from enhanced osteoprogenitor cell differentiation and activation [ 31 ].…”
Section: Biological Functions Of Pyk2mentioning
confidence: 99%
“…We and others have shown that Pyk2 genetic deletion leads to increased bone bass, through both increased bone formation by osteoblasts and decreased bone-degradation by osteoclasts [16,19]. Further, we reported that Pyk2-deficient osteoblasts show increased proliferation and mineral deposition than wild-type (WT) osteoblasts, and that the osteogenic effect of Pyk2deletion was associated with the estrogen signaling cascade [20]. Further, it was shown that ovariectomized rats treated with the chemical inhibitor PF-431396 (PF-43), which targets both Pyk2 and the related protein FAK, had increased bone formation and were protected from ovariectomy-induced bone loss [16].…”
Section: Introductionmentioning
confidence: 85%